Asymmetric Exchange Rate Pass-Through to Import and Export Prices for Turkey: A Nonlinear Autoregressive Distributed Lag (NARDL) Approach - Serdar Simonyan, (Asian Academy of Management Journal of Accounting and Finance, 2020)
This paper re-examines the exchange rate pass-through into trade prices in Turkey to observe possible asymmetries. This exercise is done using a Nonlinear Autoregressive Distributed Lag (NARDL) model. We provide empirical evidence that the impact of exchange rate into import and export prices are asymmetric, meaning that the export and import prices respond differently to a change in exchange rate depending on the direction. Moreover, we observe that the pass-through coefficients decline after Turkey adopts floating exchange rate regime. This result has important implications in terms of monetary policy.